Revisiting the Relationship Between Suicide and Unemployment in Mexico: Evidence From Linear and Non-linear Co-integration - Wang, Mei-Chih; Lin, Feng-Li; Su, Hsiu-Hui; Kuo, Pao Lan (Frontiers in Public Health, 2020)
This study attempts to investigate whether suicide-related to unemployment in Mexico using a newly developed Bootstrap ARDL bound test over the period of 1981 to 2016. To avoid omitted variable bias we use economic growth rate as a control variable. Empirical results indicate that no cointegration among these three variables and there is positively bidirectional causality between suicide rate and unemployment rate. The economic growth rate negatively affects the unemployment rate and unidirectional Granger causality running from economic growth rate to the unemployment rate in Mexico. The findings could provide valuable information for society and health policymakers to formulate the policies on suicide prevention in Mexico.